International arbitration in Italy - Benedettelli, Massimo V. (Wolters Kluwer, 2020)
"International Arbitration in Italy is the first commentary on international arbitration in Italy ever written in English. Since centuries, arbitrating cross-border business disputes has been common practice in Italy, which makes the Italian arbitration law and jurisprudence expansive and sophisticated. Italian courts have already rendered thousands of judgments addressing complex problems hidden in the regulation of arbitration. Italian jurists have been among the outstanding members of the international arbitration community, starting from when, back in 1958, Professor Eugenio Minoli was among the promoters of the New York Convention. Italy being the third-largest economy in the European Union and the eighth-largest economy by nominal GDP in the world, it also comes as no surprise that Italian companies, and foreign companies with respect to the business they do in the Italian market, are among the leading 'users' of international arbitration, nor that Italy is part to a network of more than 80 treaties aimed to protect inbound and outbound foreign direct investments and being the ground for investment arbitration cases. Moreover, in recent years, Italy has risen to prominence as a neutral arbitral seat, in particular for the settlement of 'intra-Mediterranean' disputes, also thanks to the reputation acquired by the Milan Chamber of Arbitration which has become one of the main European arbitral institutions."--